Risk, capital buffers and bank lending: The adjustment of euro area banks - Laurent Maurin; Mervi Toivanen (Journal of Banking and Financial Economics)
This paper estimates euro area banks’ internal target capital ratios and investigates whether banks’ adjustment to the targets affects their credit supply and securities holdings during the financial crisis in 2005–2011. Based on data on listed banks and country-specific macro-variables, a partial adjustment model is estimated in a panel context. The results indicate, first, that an increase in the riskiness of banks’ balance sheets positively influences banks’ target capital ratios. On the euro area level, we find banks’ undercapitalisation in terms of Tier 1 capital ratio to be close to 2 percentage points in the middle of 2008. While median capital gaps diminish towards the end of 2011, the heterogeneity across individual banks increases. Second, the adjustment towards higher equilibrium capital ratios has a significant impact on banks’ assets. The impact is more sizeable on security holdings than on loans, thereby suggesting a pecking order of bank assets for deleveraging.